A case study for upgrading existing carousel process to achieve low effluent phosphorus discharges. (1st January 2014) - Elsergany, Moetaz
In this study, Al-Qateef wastewater treatment plant was selected as a case representing the upgrade of carrousel technology with tertiary treatment. This technology is applied in many cities in the Eastern province, Kingdom of Saudi Arabia. The use of chemical treatment alternative for phosphorous removal was evaluated versus the newly implemented tertiary treatment unit. The study showed that chemical phosphorous removal has an additional advantage of reducing the final effluent total phosphorus concentration to less than 1 mg/L at an alum dose of 50 mg/L without any significant alteration of the expected final effluent quality that could be achieved by the newly installed sand filters. Furthermore, the study showed that the use of chemical treatment for phosphorous removal could reduce the chlorine dose required for the treated effluent disinfection.